2020
DOI: 10.1001/jamaoncol.2019.3388
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Quality Indicators for End-of-Life Cancer Care

Abstract: Improving the quality of cancer care is an international priority. Population-based quality indicators (QIs) are key to this process yet remain almost exclusively used for evaluating care during the early, often curative, stages of disease.OBJECTIVES To identify all existing QIs for the care of patients with cancer who have advanced disease and/or are at the end of life and to evaluate each indicator's measurement properties and appropriateness for use.EVIDENCE REVIEW For this systematic review, 5 electronic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 57 publications
(106 reference statements)
1
58
0
Order By: Relevance
“…Hence they can support the improvement of health care along the continuum of interventions by early detection coordination of multimodal regimes or providing symptomatic (palliative) care (De Roo et al 2013 ; Earle et al 2003 ). Quality indicators in the area of cancer care encompass ‘amount of inpatient deaths’ ‘extensive use of systemic chemotherapy at the EOL’ ‘admission to intensive care units (ICUs) and hospitalisations at the EOL’ or ‘lack of referral to palliative care units’ (De Schreye et al 2017 ; Earle et al 2003 2008 ; Henson et al 2020 ; Wild & Patera 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence they can support the improvement of health care along the continuum of interventions by early detection coordination of multimodal regimes or providing symptomatic (palliative) care (De Roo et al 2013 ; Earle et al 2003 ). Quality indicators in the area of cancer care encompass ‘amount of inpatient deaths’ ‘extensive use of systemic chemotherapy at the EOL’ ‘admission to intensive care units (ICUs) and hospitalisations at the EOL’ or ‘lack of referral to palliative care units’ (De Schreye et al 2017 ; Earle et al 2003 2008 ; Henson et al 2020 ; Wild & Patera 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Administrative health care data has been employed to understand quality indicators of EOL care in numerous countries, such as the United States, Japan, Sweden, Belgium, and the United Kingdom [ 4 , 5 , 6 , 7 ]. However, the specific quality indicators used vary, which limits the ability to compare quality across services or settings [ 8 ]. In light of this, a systematic review published by Henson et al evaluated 260 unique quality indicators of cancer care and found that of these, only 80 quality indicators received adequate testing to be appropriate for performance metrics.…”
Section: Introductionmentioning
confidence: 99%
“…Measures of quality EOL cancer care are explicitly defined as measurable items of practice performance used to evaluate the quality of care provided by a healthcare organization [ 9 ]. Commonly used and previously identified aggressive EOL outcomes from administrative data include hospital-centric measures such as visits to the emergency department (ED) or admission to the hospital or intensive care unit (ICU) in last 30 days of life, receiving systemic therapy within the last 14 days of life, or death in hospital [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%